Cost-utility analysis of dengue vaccination in a country with heterogeneous risk of dengue transmission - Orellano, Pablo Wenceslao; Reynoso, Julieta Itati; Stahl, Hans-Christian; Salomon, Oscar Daniel (Vaccine, 2016)
Background - Dengue is one of the most important vector-borne diseases worldwide, and annually, nearly 390 million people are infected and 500,000 patients are hospitalized for severe dengue. Argentina has great variability in the risk of dengue transmission due to eco-climatic reasons. Currently no vaccines are available for dengue even though several vaccines are under development. - Objective - The aim of this study was to estimate the cost-effectiveness of a dengue vaccine in a country with heterogeneous risk of dengue transmission like Argentina. - Methods - The analysis was carried out from a societal perspective using a Markov model that included both vaccine and disease parameters. Utility was measured as disability adjusted life years (DALYs) averted, and the incremental cost-effectiveness ratio (ICER) of the vaccination was expressed in 2014 American dollars (US$) per DALY averted. One-way and probabilistic sensitivity analyses were performed to evaluate uncertainty in model outcomes, and a threshold analysis was conducted to estimate the highest possible price of the vaccine. - Results - The ICER of the vaccination program was found to be US$ 5714 per DALY averted. This value is lower than 3 times the per capita GDP of Argentina (US$ 38,619 in 2014); 54.9% of the simulations were below this value. If a vaccination program would be implemented the maximum vaccine price per dose has to be US$1.49 for a vaccination at national level or US$28.72 for a targeted vaccination in high transmission areas. - Conclusions - These results demonstrate that vaccination against dengue would be cost-effective in Argentina, especially if carried out in predetermined regions at high risk of dengue transmission. However, these results should be interpreted with caution because the probabilistic sensitivity analysis showed that there was considerable uncertainty around the ICER value. The influence of variations in vaccine efficacy, cost and other important parameters are discussed in the text.